Analysis of genetic structure in a large sample of pomegranate (Punica granatum L.) using fluorescent SSR markers. Issue 6 (2nd November 2018) - Luo, Xiang; Cao, Shangyin; Hao, Zhaoxiang; Hou, Lefeng; Cao, Da; Zhang, Jie; Li, Haoxian; Niu, Juan; Xue, Hui; Chen, Lina
ABSTRACT: Molecular markers are helpful to efficiently protect the plant breeders' rights. Fluorescent simple sequence repeats (SSR) based on DNA sequencing is a powerful and automated platform for the detection of genetic polymorphism. Here, we first reported 13 SSRs using a fluorescent SSR panel according to the reference genome information, and detected the genetic diversity and population structure of 136 pomegranate varieties. The average number of alleles per locus was 6.31, gene diversity ranged from 0.16 to 0.37 with an average of 0.28, and polymorphic information content (PIC) varied from 0.14 to 0.29 with a mean value of 0.22. The mean genetic distance (GD) between varieties was 0.32. Population structure analysis divided the varieties into three different subpopulations (Q1, Q2, and Q3). The cultivars in Q1 all came from China, and almost all cultivars came from foreign countries combined with Chinese were grouped into Q2. The only accession originated from Myanmar was grouped to Q3. The results indicated that 13 SSR markers were polymorphic. The varieties originating from the same geographical region were more closely related, and extensive gene flow had taken place between the varieties from different regions. The results may be useful for the efficient selection breeding and variety protection.